Connectivity and neurochemistry of the commissura anterior of the pigeon (Columba livia) - Letzner, Sara (J Comp Neurol, 2015)
The anterior commissure (AC) and the much smaller hippocampal commissure constitute the only interhemispheric pathways at the telencephalic level in birds. Since the degeneration study from Zeier and Karten (1973), no detailed description of the topographic organization of the AC has been performed. This information is not only necessary for a better understanding of interhemispheric transfer in birds, but also for a comparative analysis of the evolution of commissural systems in the vertebrate classes. We therefore examined the fiber connections of the AC by using choleratoxin subunit B (CTB) and biotinylated dextran amine (BDA). Injections into subareas of the arcopallium and posterior amygdala (PoA) demonstrated contralateral projection fields within the anterior arcopallium (AA), intermediate arcopallium (AI), PoA, lateral, caudolateral and central nidopallium, dorsal and ventral mesopallium, and medial striatum (MSt). Interestingly, only arcopallial and amygdaloid projections were reciprocally organized, and all AC projections originated within a rather small area of the arcopallium and the PoA. The commissural neurons were not GABA‐positive, and thus possibly not of an inhibitory nature. In sum, our neuroanatomical study demonstrates that a small group of arcopallial and amygdaloid neurons constitute a wide range of contralateral projections to sensorimotor and limbic structures. Different from mammals, in birds the neurons that project via the AC constitute mostly heterotopically organized and unidirectional connections. In addition, the great majority of pallial areas do not participate by themselves in interhemispheric exchange in birds. Instead, commissural exchange rests on a rather small arcopallial and amygdaloid cluster of neurons. J. Comp. Neurol. 524:343–361, 2016. © 2015 The Authors The Journal of Comparative Neurology Published by Wiley Periodicals, Inc.